Bricks, trusses and superstructures: Strategies for skeletal reinforcement in batoid fishes (rays and skates) - Clark, Brett; Chaumel, Júlia; Johanson, Zerina; Underwood, Charlie; Smith, Moya M.; Dean, Mason N. (Frontiers in Cell and Developmental Biology, 2022)
Crushing and eating hard prey (durophagy) is mechanically demanding. The cartilage jaws of durophagous stingrays are known to be reinforced relative to non-durophagous relatives, with a thickened external cortex of mineralized blocks (tesserae), reinforcing struts inside the jaw (trabeculae), and pavement-like dentition. Strategies for skeletal strengthening against durophagy, however, are largely understood from myliobatiform stingrays, although a hard prey diet has evolved multiple times in batoid fishes (rays, skates, guitarfishes). We perform a quantitative analysis of micro-CT data, describing jaw strengthening mechanisms in Rhina ancylostoma (Bowmouth Guitarfish) and Rhynchobatus australiae (White spotted Wedgefish), durophagous members of the sister taxon to Myliobatiformes (Rhinopristiformes). Both species possess trabeculae, more numerous and densely packed in Rhina, albeit simpler structurally than those in stingrays like Aetobatus and Rhinoptera. Rhina and Rhynchobatus exhibit impressively thickened jaw cortices, often involving >10 tesseral layers, most pronounced in regions where dentition is thickest, particularly in Rhynchobatus. Age series of both species illustrate that tesserae increase in size during growth, with enlarged and irregular tesserae associated with the jaws’ oral surface in larger (older) individuals of both species, perhaps a feature of aging. Unlike the flattened teeth of durophagous myliobatiform stingrays, both rhinopristiform species have oddly undulating dentitions, comprised of pebble-like teeth interlocked to form compound ‘meta-teeth’ (large spheroidal structures involving multiple teeth). This is particularly striking in Rhina, where the upper/lower occlusal surfaces are mirrored undulations, fitting together like rounded woodworking finger-joints. Trabeculae were previously thought to have arisen twice independently in Batoidea; our results show they are present in all major batoid groups except the phylogenetically basal Rajiformes. Comparisons with several other durophagous and non-durophagous species illustrate that batoid skeletal reinforcement architectures are modular: trabeculae can be variously oriented and are dominant in some species (e.g. Rhina, Aetobatus), whereas cortical thickening is more significant in others (e.g. Rhynchobatus), or both features can be lacking (e.g. Raja, Urobatis). We discuss interactions and implications of character states, framing a classification scheme for exploring cartilage structure evolution in the cartilaginous fishes.